A Chronological Record of Contamination: Coral Skeletons Reveal Increasing Microplastic Diversity in Central Tapanuli, Indonesia - Rahmatsyah, Rahmatsyah; Juliani, Rita; Pranoto, Hendro; Lubis, Ali Arman; Ondara, Koko; Batubara, Agung Setia; Syavira, Riri (Trends in Sciences, 2026)
Microplastic pollution has increasingly been recognized as a critical environmental threat to coral reef ecosystems, known to disrupt feeding behavior, hinder skeletal deposition, and induce bleaching events. Despite growing awareness, little is known about how such stressors are chronologically archived within coral growth bands, particularly in regions exposed to simultaneous anthropogenic and natural pressures. This study investigates the relationship between coral growth dynamics and microplastic contamination in the coastal waters of Central Tapanuli, Indonesia an area characterized by dense human settlements (population 250,017 - 394,910), active shipping routes, and industrial growth (1,802 - 2,568 units). The research was conducted at 2 reef sites representing gradients of human influence, Karang Island and Ungge Island; coral cores were sectioned, X-rayed to visualize annual growth bands, and analyzed for embedded microplastics using stereo microscopy and Fourier Transform Infrared Spectroscopy (FTIR). Growth rates at Karang Island (2015 - 2024) ranged from 11 - 26 mm yr⁻¹, while rates at Ungge Island (2019 - 2024) were 8 - 20 mm yr⁻¹; microplastic concentrations were 3 - 20 particles g⁻¹ (Karang, 2015 - 2024) and 3 - 16 particles g⁻¹ (Ungge, 2019 - 2024). Fibers (58% - 63%) were the dominant morphology, with particle sizes ranging from 25 - 873 µm. FTIR analysis (peaks: 555 - 3,409 cm⁻¹) identified a complex polymer mixture dominated by Polystyrene (19.9%), Polypropylene (16.2%), and Polyvinyl Chloride (13.4%). Crucially, chronological analysis revealed a significant temporal trend: polymer diversity increased from 11 unique types in 2015 to 15 unique types in 2024, including new engineered plastics. The dominance of packaging-derived polymers reflects strong anthropogenic input, and this study provides the first evidence of microplastic incorporation within coral growth bands in Central Tapanuli, demonstrating that coral skeletons not only archive contamination but also record its increasing compositional complexity over time. These findings emphasize the urgent need for integrated coastal management and stricter plastic-waste regulation in Indonesia’s reef ecosystems. HIGHLIGHTS Coral bleaching on coral reef growth is influenced by anthrophogenic cause and natural cause factor. Recent research indicates that microplastics have a significant impact on coral bleaching. Microplastic particle abundance was found to be 3 - 20 particles/g on Karang Island and 3 - 16 particles/g on Ungge Island. Polystyrene (PS, 19.9%), Polypropylene (PP, 16.2%), and Polyvinyl Chloride (PVC, 13.4%) polymers who consistently become the main source of microplastics. GRAPHICAL ABSTRACT